2022
DOI: 10.3390/ijerph19116919
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 Vaccine Acceptance and Uptake in a Transborder Population at the Mexico–Guatemala Border, September–November 2021

Abstract: Assessing COVID-19 vaccination uptake of transborder populations is critical for informing public health policies. We conducted a probability (time-venue) survey of adults crossing from Mexico into Guatemala from September to November 2021, with the objective of describing COVID-19 vaccination status, willingness to get vaccinated, and associated factors. The main outcomes were receipt of ≥1 dose of a COVID-19 vaccine, being fully vaccinated, and willingness to get vaccinated. We assessed the association of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…In this study, vaccination uptake rate was increased in patients with higher level of education, which support findings from studies conducted elsewhere 27,30,49,53 . Higher educational level is known to be associated with better access and understanding of knowledge on dangerousness and prevention of diseases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, vaccination uptake rate was increased in patients with higher level of education, which support findings from studies conducted elsewhere 27,30,49,53 . Higher educational level is known to be associated with better access and understanding of knowledge on dangerousness and prevention of diseases.…”
Section: Discussionsupporting
confidence: 90%
“…The COVID-19 vaccination uptake was relatively low in the study, which is lower than that reported previously in Cameroon 24,25 and a global estimate of COVID-19 vaccination uptake rate reported by Zhang and colleagues 15 . Other studies reported higher vaccine uptake in specific groups such as elderly persons, college students and transborder populations [26][27][28] . Several factors drive the intention to accept, delay and abstain from vaccination and these include trust in vaccine approval, the perceived effectiveness of the vaccine for protecting others and conspiracy beliefs 29,30 .…”
Section: Discussionmentioning
confidence: 95%
“…This was a cross-sectional survey conducted from September 15 to November 15, 2021 in three cities on the Guatemalan side of the border (El Carmen, La Mesilla, and Tecún Umán), representing the main points of entry on the shared border (98% of all registered land arrivals in the Mexican state of Chiapas occur via these three Guatemala cities) [ 16 , 18 ]. The survey’s methods have been described in detail in a previous article describing COVID-19 vaccination and acceptance [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…4,5 A total of 200,000,000 doses have been administered, which roughly approximates to threequarters of the population receiving a dose. 6,7 Even so, Latin America continues to have a disproportionate burden of disease. 8,9 Mexico has increased comorbidities and age.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, over 7 million confirmed cases of COVID‐19 and over 300,000 have occurred in Mexico 4,5 . A total of 200,000,000 doses have been administered, which roughly approximates to three‐quarters of the population receiving a dose 6,7 . Even so, Latin America continues to have a disproportionate burden of disease 8,9 …”
Section: Introductionmentioning
confidence: 99%